2013
DOI: 10.1159/000357948
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes in Spleens and Livers of Tumour-Bearing Mice Suggest Delayed Inflammation and Attenuated Cachexia in Response to Oil Palm Phenolics

Abstract: Background/Aim: Plant phenolics can inhibit, retard or reverse carcinogenesis, and may thus help prevent or treat cancer. Oil palm phenolics (OPP) previously showed anti-tumour activities in vivo via a cytostatic mechanism at 1,500 ppm gallic acid equivalent. Here, we report other possible molecular mechanisms by which this extract attenuates cancer, especially those concerning the immune response. Methods: We subcutaneously injected J558 myeloma cells in BALB/c mice and supplemented OPP orally at 1,500 ppm ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 173 publications
(115 reference statements)
1
6
0
Order By: Relevance
“…Recently, a water soluble antioxidant preparation rich in polyphenolics has been recovered from this waste in an attempt to transform this heavy bio-burden into a series of high value bio-products (Sambanthamurthi, Sundram, & Tan, 2008a). For example, recent studies have identified a range of beneficial biological outcomes of oil palm phenolics (OPP) including antioxidant, antiinflammatory, anti-diabetic, neuro-protective as well as vascular protective qualities (Abeywardena et al, 2002;Bolsinger, Pronczuk, Sambanthamurthi, & Hayes, 2014;Leow, Sekaran, Sundram, Tan, & Sambanthamurthi, 2013a;Leow, Sekaran, Tan, Sundram, & Sambanthamurthi, 2013b;Nasef, Mehta, Murray, Marlow, & Ferguson, 2014;Sambanthamurthi et al, 2011). These observation for OPP are in agreement with several other plant extracts and isolated polyphenols and flavonoids reported to exert biological actions on various cardiac (Fang et al, 2011;Wallace, Baczko, Jones, Fercho, & Light, 2006;Wu, Loh, Cheng, Lu, & Lin, 2013) and vascular smooth muscle cell preparations including modulation of contractility (Diebolt & Andriantsitohaina, 2002;Protic et al, 2013;Zhu, Wang, Ou, Han, & Li, 2013).…”
Section: Introductionsupporting
confidence: 65%
“…Recently, a water soluble antioxidant preparation rich in polyphenolics has been recovered from this waste in an attempt to transform this heavy bio-burden into a series of high value bio-products (Sambanthamurthi, Sundram, & Tan, 2008a). For example, recent studies have identified a range of beneficial biological outcomes of oil palm phenolics (OPP) including antioxidant, antiinflammatory, anti-diabetic, neuro-protective as well as vascular protective qualities (Abeywardena et al, 2002;Bolsinger, Pronczuk, Sambanthamurthi, & Hayes, 2014;Leow, Sekaran, Sundram, Tan, & Sambanthamurthi, 2013a;Leow, Sekaran, Tan, Sundram, & Sambanthamurthi, 2013b;Nasef, Mehta, Murray, Marlow, & Ferguson, 2014;Sambanthamurthi et al, 2011). These observation for OPP are in agreement with several other plant extracts and isolated polyphenols and flavonoids reported to exert biological actions on various cardiac (Fang et al, 2011;Wallace, Baczko, Jones, Fercho, & Light, 2006;Wu, Loh, Cheng, Lu, & Lin, 2013) and vascular smooth muscle cell preparations including modulation of contractility (Diebolt & Andriantsitohaina, 2002;Protic et al, 2013;Zhu, Wang, Ou, Han, & Li, 2013).…”
Section: Introductionsupporting
confidence: 65%
“…Additionally, R. oryzae has been reported to produce substantial amounts of various antioxidants and organic acids, including gallic acid [ 48 ]. Interestingly, an extract of oil palm phenolics (OPP), containing 1500 ppm gallic acid equivalent, has been shown to inhibit tumorigenesis, by mediating G1/S phase cell cycle arrest, delay inflammatory responses and attenuate cachexia symptoms in tumor-bearing mice [ 49 ]. Gallic acid has also been shown to improve glucose tolerance and triglyceride concentration in obese mice [ 49 ] and suppress lipogenesis in humans, while concomitantly combating pro-inflammatory responses [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, R. oryzae has been reported to produce substantial amounts of various antioxidants and organic acids, including gallic acid (76). Interestingly, an extract of oil palm phenolics (OPP), containing 1,500 ppm gallic acid equivalent, has been shown to inhibit tumorigenesis, by mediating G1/S phase cell cycle arrest, delay inflammatory responses and attenuate cachexia symptoms in tumorbearing mice (77,78). Gallic acid has also been shown to improve glucose tolerance and triglyceride concentration in obese mice (79) and suppress lipogenesis in humans, while concomitantly combating pro-inflammatory responses (80).…”
Section: Discussionmentioning
confidence: 99%